Kualitas Pelayanan Check-In Dan Check-Out Tamu Hotel Kelas Melati di Palembang - Nyayu Ully Auliana; Dwi Hanadya (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This study was conducted to determine the quality of guest check-in and check-out services at Palembang jasmine class hotels. When making a reservation, check-in and check-out a receptionist will follow the hotel's Standard Operating Procedures. In this case, the Standard Operating Procedures are rules that must be carried out by all hotel employees in order to provide the desired quality of service. Jasmine class hotels in Palembang in checking in and checking out guests still have not implemented standard operational service procedures. This has an impact on the quality of service, such as allowing guests to have their needs for service not met. Therefore, a standard procedure for hotel check-in and check-out services has been prepared which is expected to improve the quality of service and meet the needs of hotel guests.